Active server pages black book - Williams, Al (Coriolis Group, Inc., 1988)
Covers Active Server Pages, HTML (including Dynamic HTML), scripting, ActiveX controls, Java applets, Internet Information Server, and Internet Explorer. Compares the differences between Microsoft's JScript and Netscape's JavaScript. Covers pacesetting, yet hard-to-find, information on DHTML and IIS 4.0 technologies